Adrenoreceptors and nitric oxide in the cardiovascular system - Conti, Valeria; Russomanno, Giusy; Corbi, Graziamaria; Izzo, Viviana; Vecchione, Carmine; Filippelli, Amelia (Frontiers in Physiology, 2013)
Nitric Oxide (NO) is a small molecule that continues to attract much attention from the scientific community. Since its discovery, it has been evident that NO has a crucial role in the modulation of vascular tone. NO is involved in multiple signal transduction pathways thus contributing to the regulation of many cellular functions. NO effects can be either dependent or independent on cGMP, and rely also upon several mechanisms such as the amount of NO, the compartmentalisation of the enzymes responsible for its biosynthesis (NOS), and the local redox conditions. Several evidences highlighted the correlation among adrenoreceptors activity, vascular redox status and NO bioavailability. It was suggested a possible crosstalk between NO and oxidative stress hallmarks in the endothelium function and adaptation, and in sympathetic vasoconstriction control. Adrenergic vasoconstriction is a balance between a direct vasoconstrictive effect on smooth muscle and an indirect vasorelaxant action caused by α2- and β-adrenergic endothelial receptor-triggered NO release. An increased oxidative stress and a reduction of NO bioavailability shifts this equilibrium causing the enhanced vascular adrenergic responsiveness observed in hypertension. The activity of NOS contributes to manage the adrenergic pathway, thus supporting the idea that the endothelium might control or facilitate β-adrenergic effects on the vessels and the polymorphic variants in β2-receptors and NOS isoforms could influence aging, some pathological conditions and individual responses to drugs. This seems to be dependent, almost in part, on differences in the control of vascular tone exerted by NO. Given its involvement in such important mechanisms, the NO pathway is implicated in aging process and in both cardiovascular and non-cardiovascular conditions. Thus, it is essential to pinpoint NO involvement in the regulation of vascular tone for the effective clinical/therapeutic management of cardiovascular diseases.